Depressive Disorders and Religious Engagement in Very Old People. (May 2019) - Strinnholm, Sofia; Gustafson, Yngve; Niklasson, Johan
Objective: To examine associations between religious engagement and depressive disorders in very old people.Method: This cross-sectional study uses data from the Umeå 85+/Gerontological Regional Database (GERDA) study. Every other 85-year-old, every 90-year-old, and everyone more than 95 years from eight municipalities in northern Sweden and Finland were invited: 1, 014 persons accepted participation. Data were gathered using questionnaires and assessment scales during structured home visits.Results: The prevalence of depressive disorders was 35.8%. In a logistic regression model, several factors were adjusted for, such as demographic variables including social factors, diseases, and cognitive and physical functional level. A high level of self-reported religious engagement was independently associated with not having depressive disorders (odds ratio [OR] = 0.58, confidence interval [CI] = [0.38, 0.89]). After stratifying by gender, religious engagement was only significant for women (OR = 0.49, CI = [0.29, 0.82]).Discussion: There is an association between a high level of religious engagement and being free from diagnosis of depressive disorders among very old women.